Radiological versus laparoscopic insertion of peritoneal dialysis catheter: a study comparing outcomes at a single centre. Issue 11 (24th August 2022) - Sia, Yi; Hodgson, Russell; Kuder, Paula; Tog, Chek
Abstract: Background: Although peritoneal dialysis (PD) is a well‐established and effective form of renal replacement therapy in end‐stage renal failure (ESRF) patients, there is no consensus as to the optimal insertion technique. This study compares the outcomes of PD catheters inserted radiologically versus laparoscopically at a single centre. Methods: Patients who underwent either radiological PD catheter insertion (RC) or laparoscopic insertion (LC) between 2013 and 2019 were retrospectively reviewed. Primary outcome was catheter patency at 12 months. Secondary outcomes included exit‐site infections, peritonitis, and pericatheter leaks within 30 days of insertion, any complications associated with insertion, overall catheter survival, and inpatient length of stay (LoS). Results: There were 81 patients included in this study, with a total of 100 procedures performed (RC = 48, LC = 52). There were significantly fewer overall complications in the LC group compared to the RC group ( P < 0.001). However, when individual complications were considered, this significant difference was only seen in the rate of malpositioned catheters (10.4% versus 0%, P = 0.023). Hospital LoS was longer in the LC group compared to the RC group (3 versus 2 days, P = 0.004), but this was outweighed by the fact that there were more laparoscopically inserted PD catheters still functioning and patent at 12 months compared to those inserted radiologically. Conclusion: This study has demonstrated that our laparoscopic PD catheter insertion technique of securing the catheter tip low in the pelvis is safe and effective, providing a lower complication rate and longer‐term viability when compared to the radiological percutaneous approach. Abstract : This is a retrospective study comparing outcomes of radiological vs. laparoscopic peritoneal dialysis catheter insertion. It can be concluded that the laparoscopic method is a safe and effective technique with an overall lower complication rate and a higher long‐term durability when compared to the radiological percutaneous approach when using a meticulous and improved surgical technique.